dialogues of styles - Lidin, Konstantin (project baikal, 2024)
Every major style goes through a series of metamorphoses after its inception. Styles echo each other, learn from each other, argue and penetrate each other. The selection of materials in this section contains the results of historical observations and research, showing these processes on specific examples. How was the great style of classicism reflected in the works of its fiery overthrowers? How was the Enlightenment style transformed on the Far Eastern land? How did Russian architects influence the new architecture of China? How is the cultural heritage of Soviet and German cities reinterpreted? All these materials are united by the theme of the dialogue of styles and the metamorphoses that arise in this process.